Analyses of natural courses of Japanese patients with Alzheimer's disease using placebo data from placebo‐controlled, randomized clinical trials: Japanese Study on the Estimation of Clinical course of Alzheimer's disease. Issue 1 (1st January 2019) - Watanabe, Mitsunori; Nakamura, Yu; Yoshiyama, Yasumasa; Kagimura, Tatsuo; Kawaguchi, Hiroyuki; Matsuzawa, Hiroshi; Tachibana, Yosuke; Nishimura, Kazuma; Kubota, Naoki; Kobayashi, Masato; Saito, Takayuki; Tamura, Kaoru; et al.
Abstract: Introduction: Symptomatic anti‐Alzheimer's disease (AD) drugs have been commonly used for the treatment of AD. Knowing the natural courses of patients with AD on placebo is highly relevant for clinicians to understand their efficacy and for investigators to design clinical studies. Methods: The data on rating scales for dementia such as Alzheimer's Disease Assessment Scale‐cognitive subscale (ADAS‐cog) and Severe Impairment Battery were extracted from eight previous Japanese Phase II and III studies. Natural courses of Japanese AD patients in placebo groups were evaluated and statistically analyzed in a pooled and retrospective fashion. Results: Decreases in ADAS‐cog and Severe Impairment Battery was larger at week 22 or 24 than at week 12. Scores of ADAS‐cog appeared to deteriorate faster in moderate AD than in mild AD. Discussion: The present data will provide clinicians following up patients with AD with helpful information on how to manage AD patients and investigators with instruction for clinical study design.